2009
DOI: 10.1080/01612840903050414
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Video/Computer Game Use: Relations with School Performance and Behavior

Abstract: This study examined the amount and content of children's video game playing in relation with behavioral and academic outcomes. Relationships among playing context, child gender, and parental monitoring were explored. Data were obtained through parent report of child's game play, behavior, and school performance. Results revealed that time spent playing games was related positively to aggression and negatively to school competence. Violent content was correlated positively and educational content negatively wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 48 publications
(70 reference statements)
7
81
1
5
Order By: Relevance
“…This finding is similar to those of other students within the literature (Chiu et al, 2004;Hastings et al, 2009;Rehbein et al, 2010;Skoric et al, 2009). Both in this study's and in the findings of related studies, it is observed that video game addiction influences students' academic performance negatively.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is similar to those of other students within the literature (Chiu et al, 2004;Hastings et al, 2009;Rehbein et al, 2010;Skoric et al, 2009). Both in this study's and in the findings of related studies, it is observed that video game addiction influences students' academic performance negatively.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is similar to that of Hastings et al (2009) and that of Bilge (2012). One of the symptoms of video game addiction is that an individual spends more time than necessary on the computer.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Considering that the amount of time spent in playing video games is associated with poorer academic performance [66,67], we can introduce our idea about the use of action video game (AVG) to improve reading abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan araştırmalarda, 6 yaşındaki çocukların %27'sinin (Erbay & Durmuşoğlu Saltalı, 2012); 5-6 yaş aralığındaki çocukların %73,1'inin (Akçay & Özcebe, 2012); 6-15 yaş aralığındaki çocukların %83,2'sinin (Türkiye İstatistik Kurumu [TUİK], 2014); 13-19 yaş aralığındaki çocukların %50,3'ünün (Mathers, Sci, Canterford, Olds, Hesketh, Ridley & Wake, 2009) her gün elektronik oyun oynadıkları belirlenmiştir. Çocukların gün içindeki elektronik oyun oynama sürelerini inceleyen araştırmalarda; Amerika'da 6-17 yaş aralığındaki çocukların her gün 0.95 ±0.01 saat (Russ, Larson, Franke & Halfon, 2009); 4-6 yaş aralığındaki çocukların hafta içi 0.53±0.53, hafta sonu 1.62±1.56 saat (Akçay & Özcebe, 2012); Amerika'da 6-10 yaş aralığındaki çocukların her hafta 3.4±2.8 saat (Hastings, Karas, Winsler, Way, Amy & Tyler, 2009) elektronik oyun oynadığı belirlenmiştir. Bu araştırmada ise, 5-12 yaş aralığındaki çocukların her gün ortalama 2.00 ±0.56 saat elektronik oyun oynadığı belirlendi (Tablo 2).…”
Section: Discussionunclassified